Cloning and characterization of an alternative splicing transcript of the gene coding for human cytidine deaminase - Lisboa, Blanca Cristina Garcia (2007)
Human cytidine deaminase (HCD) catalyzes the deamination of cytidine or deoxycytidine to uridine or deoxyuridine, respectively. the genomic sequence of HCD is formed by 31 kb with 4 exons and several alternative splicing signals, but an alternative form of HCD has yet to be reported. Here we describe the cloning and characterization of a small form of HCD, HSCD, and it is likely to be a product of alternative splicing of HCD. the alignment of DNA sequences shows that the HSCD matches HCD in 2 parts, except for a deletion of 170 bp. Based on the HCD genome organization, exons I and 4 should be joined and all sequences of introns and exons 2 and 3 should be deleted by splicing. This alternative splicing shifted the translation of the reading frame from the point of splicing. the estimated molecular mass is 9.8 kDa, and this value was confirmed by Western blot and mass spectroscopy after expressing the gene fused with glutathionine-S-transferase in the pGEX vector. the deletion and shift of the reading frame caused a loss of HCD activity, which was confirmed by enzyme assay and also with NIH3T3 cells modified to express HSCD and challenged against cytosine arabinoside. in this work we describe the identification and characterization of HSCD, which is the product of alternative splicing of the HCD gene.